Predictors of Picture Naming and Picture Categorization in Spanish - Macarena Martínez Cuitiño; Federico Gonzalo Soriano; Virginia Jaichenco; Brenda Steeb; Juan Pablo Barreyro (East European Journal of Psycholinguistics, 2019)
The aim of this paper was to identify which psycholinguistic variables are better predictors of performance for healthy participants in a picture naming task and in a picture categorization task. A correlation analysis and a Path analysis were carried out. The correlation analysis showed that naming accuracy and naming latency are significant and positively correlated with lexical frequency and conceptual familiarity variables, whereas they are negatively correlated with H index. Reaction times in the categorization task were negatively correlated with lexical frequency and conceptual familiarity variables and positively correlated with visual complexity variable. The Path analysis showed that subjective lexical frequency and H index are the better predictors for picture naming task. In picture categorization task, for reaction times, the better predictor variables were subjective lexical frequency, conceptual familiarity and visual complexity. These findings are discussed considering previous works on the field. References Akinina, Y., Malyutina, S., Ivanova, M., Iskra, E., Mannova, E., & Dragoy, O. (2015). Russian normative data for 375 action pictures and verbs. Behavior research methods, 47(3), 691-707. doi: 10.3758/s13428-014-0492-9 Alario, F. X., & Ferrand, L. (1999). A set of 400 pictures standardized for French: Norms for name agreement, image agreement, familiarity, visual complexity, image variability, and age of acquisition. Behavior Research Methods, Instruments, & Computers, 31(3), 531-552. Alario, F. X., Ferrand, L., Lagnaro, M., New, B., Frauenfelder, U. H., & Seguí, J. (2004). Predictors of picture naming speed. Behavior Research Methods, Instruments and Computers, 36, 140-155. doi: 10.3758/BF03195559 Albanese, E., Capitani, E., Barbarotto, R., & Laiacona, M. (2000). Semantic category dissociations, familiarity and gender. Cortex, 36, 733-746. Almeida, J., Knobel, M., Finkbeiner, M., & Caramazza, A. (2007). The locus of the frequency effect in picture naming: When recognizing is not enough. Psychonomic Bulletin & Review, 14(6), 1177-1182. Arbuckle, J. L. (2003). AMOS 5.0. Chicago: SmallWaters. Bakhtiar, M., & Weekes, B. (2015). Lexico-semantic effects on word naming in Persian: Does age of acquisition have an effect? Memory & Cognition, 43(2), 298-313. doi: 10.3758/s13421-014-0472-4 Balota, D. A., Pilotti, M., & Cortese, J. M. (2001). Subjective frequency estimates for 2,938 monosyllabic words. Memory & Cognition, 29, 639-647. doi: 10.3758/BF03200465 Barbón, A., & Cuetos, F. (2006). Efectos de la Edad de Adquisición en tareas de Categorización Semántica. Psicológica, 27, 207-223. Barca, L., Burani, C., & Arduino, L. (2002). Word naming times and psycholinguistic norms for Italian nouns. Behavior Research Methods, Instruments and Computers, 34(3), 424-434. Barry, C., Morrison, C. M., & Ellis, A. W. (1997). Naming the Snodgrass and Vanderwart pictures: Effects of age of acquisition, frequency and name agreement. Quarterly Journal of Experimental Psychology, 50(A), 560-585. Bates, E., Burani, C., D´amico, S., & Barca, L. (2001). Word reading and picture naming in Italian. Memory and Cognition, 29(7), 986-999. Bates, E., D’Amico, S., Jacobsen, T., Székely, A., Andonova, E., Devescovi, A., . . . Tzeng, O. (2003). Timed picture naming in seven languages. Psychonomic Bulletin & Review 20(2), 344-380. doi: 10.3758/BF03196494 Berman, S., Friedman, D., Hamberger, M., & Snodgrass, J. G. (1989). Developmental picture norms: Relationships between name agreement, familiarity, and visual complexity for child and adult ratings of two sets of line drawings. Behavior Research Methods, Instruments, & Computers, 21(3), 371-382. Bonin, P., Boyer, B., Méot, A., Fayol, M., & Droit, S. (2004). Psycholinguistic norms for action photographs in French and their relationships with spoken and written latencies. Behavior Research Methods, Instruments, & Computers, 36, 127-139. doi: 10.3758/BF03195558 Bonin, P., Chalard, M., Méot, A., & Fayol, M. (2002). The determinants of spoken and written picture naming latencies. British Journal of Psychology, 93, 89-114. doi: 10.1348/ 000712602162463 Bonin, P., Peereman, R., Malardier, N., Méot, A., & Chalard, M. (2003). A new set of 299 pictures for psycholinguistic studies: French norms for name agreement, image agreement, conceptual familiarity, visual complexity, image variability, age of acquisition and naming latencies. Behavior Research Methods, Instruments, & Computers, 35, 158-167. Boukadi, M., Zouaidi, C., & Wilson, M. A. (2016). Norms for name agreement, familiarity, subjective frequency, and imageability for 348 object names in Tunisian Arabic. Behavior Research Methods, 48, 585-599. doi: 10.3758/s13428-015-0602-3 Brysbaert, M., Van Wijnendaele, I., & De Deyne, S. (2000). Age-of-acquisition effects in semantic processing tasks. Acta Psychologica, 104, 215-226. doi: 10.1016/S0001-6918(00)00021-4 Cameirão, M. L., & Vicente, S. G. (2010). Age-of-acquisition norms for a set of 1,749 Portuguese words. Behavior Research Methods, 42, 474-480. doi: 10.3758/BRM.42.2.474 Capitani, E., Laiacona, M., Barbarotto, R., & Trivelli, C. (1994). Living and nonliving categories: Is there a “normal” asymmetry? Neuropsychologia, 32, 1453-1463. Carroll, J. B., & White, M. N. (1973). Word frequency and age of acquisition as determiners of picture-naming latency. Quarterly Journal of Experimental Psychology, 25(1), 85-95. doi: 10.1080/14640747308400325 Cuetos, F., & Barbón, A. (2006). Word naming in Spanish. European Journal of Cognitive Psychology, 18, 415-436. Cuetos, F., Ellis, A., & Alvarez, B. (1999). Naming times for the Snodgrass and Vanderwart pictures in Spanish. Behavior Research Methods, Instruments and Computers, 31, 650-658. doi: 10.3758/BF03200741 Cycowicz, Y. M., Friedman, D., Rothstein, M., & Snodgrass, J. G. (1997). Picture naming by young children: Norms for name agreement, familiarity, and visual complexity. Journal of Experimental Child Psychology, 65(2), 171-237. doi: 10.1006/jecp.1996.2356 D´amico, S., Devescovi, A., & Bates, E. (2001). Picture naming and lexical access in italian children and adults. Journal of Cognition and Development, 2(1), 71-105. Dell´Acqua, R., Lotto, L., & Job, R. (2000). Naming times and standardized norms for the Italian PD/DPSS set of 266 pictures. Direct comparisons with American, English, French and Spanish published databases. Behavior Research Methods, Instruments, & Computers, 31, 588-615. Ellis, A. W., & Morrison, C. M. (1998). Real age of acquisition effects in lexical retrieval. Journal of Experimental Psychology: Learning, Memory & Cognition, 24, 515-523. doi: 10.1037/0278-7393.24.2.515 Forster, K. I., & Forster, J. C. (2003). DMDX: A Windows display program with millisecond accuracy. Behavior Research Methods Instruments and Computers, 35, 116-124. doi: 10.3758/BF03195503 Gaffan, D., & Heywood, C. (1993). A spurious category-specific visual agnosia for living things in normal human and nonhuman primates. Journal of Cognitive Neuroscience, 5(118-128). doi: 10.1162/jocn.1993.5.1.118 Humphreys, G. W., Riddoch, M. J., & Quinlan, P. T. (1988). Cascade processes in picture identification. Cognitive Neuropsychology, 5(1), 67-103. Iyer, G., Saccuman, C., Bates, E., & Wulfeck, B. (2001). A Study of Age-of-acquisition (AoA) Ratings in Adults. CRL Newsletter, 13(2), 3-16. Khwaileh, T., Body, R., & Herbert, R. (2014). A normative database and determinants of lexical retrieval for 186 Arabic nouns: Effects of psycholinguistic and morpho-syntactic variables on naming latency. Journal of Psycholinguistic Research, 43, 749-769. doi: 10.1007/ s10936-013-9277-z Khwaileh, T., Mustafawi, E., Herbert, R., & Howard, D. (2018). Gulf Arabic nouns and verbs: A standardized set of 319 object pictures and 141 action pictures, with predictors of naming latencies. Behavior Research Methods, 50(6), 2408-2425. doi: 10.3758/s13428-018-1019-6 Laws, K. R. (1999). Gender afects latencies for naming living and nonliving things: implications for familiarity. Cortex, 35, 729–733. Laws, K. R. (2000). Category-specificity naming errors in normal subjects: The influence of evolution and experience. Brain and Language, 75, 123-133. doi: 10.1006/brln.2000.2348 Laws, K. R., & Neve, C. (1999). A `normal` category-specific advantage for naming living things. Neuropsychologia, 37, 1263-1269. doi: 10.1016/S0028-3932(99)00018-4 Lloyd-Jones, T. J., & Humphreys, G. W. (1997). Perceptual differentiation as a source of category effects in object processing: evidence from naming and object decision. Memory and Cognition, 25, 18-35 doi: 10.3758/BF03197282 Manoiloff, L., Artstein, M., Canavoso, M., Fernández, L., & Seguí, J. (2010). Expanded norms for 400 experimental pictures in an Argentinean Spanish-speaking population. Behavior Research Methods, 42(2), 452-460. doi: 10.3758/BRM.42.2.452 Martein, R. (1995). Norms for name and concept agreement, familiarity, visual complexity and image agreement on a set of 216 pictures. Psychologica Belgica, 35, 205-225. Martínez-Cuitiño, M., Barreyro, J. P., Wilson, M., & Jaichenco, V. (2015). Nuevas normas semánticas y de tiempos de latencia para un set de 400 dibujos en español. Interdisciplinaria, 32(2), 289-305. Martínez-Cuitiño, M., & Vivas, L. (In press). Category or diagnosticity effect? The influence of color in picture naming tasks. Psychology and Neuroscience. doi: 10.1037/pne0000172 Meschyan, G., & Hernandez, A. (2002). Age of acquisition and word frequency: Determinants of object-naming speed and accuracy. Memory & Cognition, 30, 262-269. doi: 10.3758/ BF03195287 Morrison, C. M., Chappell, T. D., & Ellis, A. W. (1997). Age of Acquisition Norms for a Large Set of Object Names and Their Relation to Adult Estimates and Other Variables. The Quarterly Journal of Experimental Psychology Section A: Human Experimental Psychology, 50(3), 528-559. doi: 10.1080/027249897392017 Morrison, C. M., Ellis, A. W., & Quinlan, P. T. (1992). Age of acquisition, not word frequency, affects object naming, not object recognition. Memory and Cognition, 20, 705-714. doi: 10.3758/BF03202720 Oldfield, R. C., & Wingfield, A. (1965). Response latencies in naming objects. Quart J Exp Psychol`, 17, 273-281. doi: 10.1080/17470216508416445 Protopapas, A. (2007). Check Vocal: A program to facilitate checking the accuracy and response time of vocal responses from DMDX. Behavior Research Methods, 39(4), 859-862. doi: 10.3758/BF03192979 Sanfeliu, M. C., & Fernández, A. (1996). A set of 254 Snodgrass-Vanderwart pictures standardized for Spanish: Norms for name agreement, image agreement, familiarity, and visual complexity. Behavior Research Methods, Instruments, & Computers, 28, 537-555. Shao, Z., Roelofs, A., & Meyer, A. S. (2012). Sources of individual differences in the speed of naming objects and actions: The contribution of executive control. The Quarterly Journal of Experimental Psychology, 65(10), 1927-1944. Snodgrass, J. G., & Vanderwart, M. (1980). A standardized set of 260 pictures: Norms for name agreement, image agreement, familiarity and visual complexity. Journal of Experimental Psychology: Human Learning and Memory, 6, 174-215. doi: 10.1037//0278-7393.6.2.174 Snodgrass, J. G., & Yuditsky, T. (1996). Naming times for the Snodgrass and Vanderwart pictures. Behavior Research Methods, Instruments, y Computers, 28(4), 516-536. Székely, A., & Bates, E. (2000). Objective Visual Complexity as a Variable in Studies of Pictures Naming. CLR Newsletter, 12(2), 3-33. Székely, A., D’Amico, S., Devescovi, A., Federmeier, K., Herron, D., Iyer, G., . . . Bates, E. (2003). Timed picture naming: Extended norms and validation against previous studies. Behavior Research Methods, Instruments, & Computers, 35, 621-633. doi: 10.3758/ BF03195542 Tanaka-Ishii, K., & Terada, H. (2011). Word familiarity and frequency. Studia Linguistica, 65(1), 96-116. doi: 10.1111/j.1467-9582.2010.01176.x Vitkovitch, M., & Tyrrell, L. (1995). Sources of disagreement in object naming. Quarterly Journal of Experimental Psychology, 48(A), 822-848. doi: 10.1080/14640749508401419 Warrington, E. K., & McCarthy, R. A. (1983). Category-specific access dysphasia. Brain, 106, 859-879. doi: 10.1093/brain/106.4.859